The Role of Islamic EducationTeacher in improving The Morals of Junior High School Student - eka wulandari; Ikhwan Aziz Q; Rina Mida Hayati (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2023)
Abstrack Morals are a priority in Islam. This is based on the rule that the Prophet Muhammad was sent to the world as one of his main missions to perfect morals. In achieving a person's moral perfection, guidance is needed through education, namely Islamic education. There is a problem, namely some grade VIII students of SMP Ma'arif Ansoru Al-Hasaniyah who have bad behavior towards friends, teachers and do not obey school rules. This study aims to determine the role of Islamic education teachers in improving the morals of class VIII students at SMP Ma'arif Ansoru Al-Hasaniyah Rumbia. The type of research used by the author is a qualitative field research (field research). Data collection techniques used in this study were interviews/interviews, documentation and observation. The results of the study can be concluded that the role of the PAI teacher in improving the morals of class VIII students at SMP Ma'arif Ansoru Al-Hasaniyah Rumbia. That PAI teachers carry out their duties in a professional, responsible, patient and sincere manner. So that class VIII students at SMP Ma'arif Ansoru Al-Hasaniyah Rumbia, who used to have poor morals, are now better, now they become individuals who have a polite attitude